Pengaruh Pengungkapan Corporate Social Responsibility dan Karakteristik Perusahaan terhadap Agresivitas Pajak - Agustina, Belinda; Widiatmoko, Jacobus; Kentris Indarti, Maria Goreti (Universitas Muhammadiyah Metro, 2024)
This research aims to assess the consequences of corporate social responsibility disclosure, profitability, leverage, and company size on tax aggressiveness. The focus of the research is on manufacturing companies in the basic industrial and chemical sectors listed on the Indonesia Stock Exchange during the 2019-2022 period. Sample selection was carried out using the purposive sampling method, resulting in 127 companies. The data analyzed comes from secondary data taken from financial reports and company annual reports. Data analysis includes descriptive approaches and multiple linear regression. The results of the research using CETR measurements, disclosure of corporate social responsibility and leverage have a positive impact. On the other hand, profitability and company size show a negative impact. The results of the research using the ETR measurement, disclosure of corporate social responsibility and profitability have a negative impact, leverage has a positive impact, and company size has no significant effect